2015
DOI: 10.3390/w7020568
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Hydraulic Behaviour of Growing Media with the Explicit Finite Volume Solution

Abstract: Abstract:The increasing imperviousness of urban areas reduces the infiltration and evapotranspiration capacity of urban catchments and results in increased runoff. In the last few decades, several solutions and techniques have been proposed to prevent such impacts by restoring the hydrological cycle. A limiting factor in spreading the use of such systems is the lack of proper modelling tools for design, especially for the infiltration processes in a growing medium. In this research, a physically-based model, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Because actual ET rates in the Northeast U.S. are typically constrained by moisture availability and not energy, a two-step process was developed to generate a time series of Actual Evapotranspiration (AET) time series for use in the SWMM simulations. The first step involved computing a PET time series by inserting the monitored rooftop air temperature (T) and solar radiation (R a ) values into the Hargreaves equation [32]:…”
Section: Rainfall-runoff Modeling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Because actual ET rates in the Northeast U.S. are typically constrained by moisture availability and not energy, a two-step process was developed to generate a time series of Actual Evapotranspiration (AET) time series for use in the SWMM simulations. The first step involved computing a PET time series by inserting the monitored rooftop air temperature (T) and solar radiation (R a ) values into the Hargreaves equation [32]:…”
Section: Rainfall-runoff Modeling Approachmentioning
confidence: 99%
“…Modeling approaches have advanced in number and sophistication since 2007, when Elliot and Trowsdale [26] reported that only one model (e.g., Water Balance Model) could be used to model green roof hydrology explicitly. Recent modeling efforts represent green roof storm water attenuation using runoff coefficients or curve numbers [27][28][29][30] and use more elaborate physically-based models such as HYDRUS-1D (Prague, Czech Republic) [31][32][33] to represent saturated and unsaturated flow patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, existing tools do not incorporate automatic parameter optimization techniques and sensitivity analysis routines, which have proven to be fundamental when the model includes multiple parameters. In recent years, researchers have focused their attention on applying and developing physicallybased models for the LID analysis (Carbone et al, 2015a), however more research is still needed in this direction.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic models have proven to be a valid and reliable alternative to conceptual and analytical models for the analysis of green roofs and LIDs in general. Carbone et al (2015a) developed a one‐dimensional finite volume model for description of the infiltration process during rainfall events in green roof substrates. The model was based on the reduced advective form of the Richards equation, in which the soil water diffusivity was neglected.…”
mentioning
confidence: 99%